Occurrence, Risk Factors, and Outcomes of Pulmonary Barotrauma in Critically Ill COVID-19 Patients: A Retrospective Cohort Study. (22nd February 2023) - Al-Dorzi, Hasan M.; Al Mejedea, Haifa; Nazer, Reema; Alhusaini, Yara; Alhamdan, Aminah; Al Jawad, Ajyad
Abstract : Objective . Pulmonary barotrauma has been frequently observed in patients with COVID-19 who present with acute hypoxemic respiratory failure. This study evaluated the prevalence, risk factors, and outcomes of barotrauma in patients with COVID-19 requiring ICU admission. Methods . This retrospective cohort study included patients with confirmed COVID-19 who were admitted to an adult ICU between March and December 2020. We compared patients who had barotrauma with those who did not. A multivariable logistic regression analysis was performed to determine the predictors of barotrauma and hospital mortality. Results . Of 481 patients in the study cohort, 49 (10.2%, 95% confidence interval: 7.6–13.2%) developed barotrauma on a median of 4 days after ICU admission. Barotrauma manifested as pneumothorax ( N = 21), pneumomediastinum ( N = 25), and subcutaneous emphysema ( N = 25) with frequent overlap. Chronic comorbidities and inflammatory markers were similar in both patient groups. Barotrauma occurred in 4/132 patients (3.0%) who received noninvasive ventilation without intubation, and in 43/280 patients (15.4%) who received invasive mechanical ventilation. Invasive mechanical ventilation was the only risk factor for barotrauma (odds ratio: 14.558, 95% confidence interval: 1.833–115.601). Patients with barotrauma had higher hospital mortality (69.4% versus 37.0%; p < 0.0001 ) and longer duration of mechanical ventilation and ICU stay. Barotrauma was an independent predictor of hospital mortality (odds ratio: 2.784, 95% confidence interval: 1.310–5.918). Conclusion s. Barotrauma was common in critical COVID-19, with invasive mechanical ventilation being the most prominent risk factor. Barotrauma was associated with poorer clinical outcomes and was an independent predictor of hospital mortality.